Expanded description of Odorrana livida (Blyth, 1856) with notes on its natural history in Thailand. Issue 23 (26th June 2018) - Rujirawan, Attapol; Stuart, Bryan L.; Aowphol, Anchalee
ABSTRACT: The South East Asian cascade frog Odorrana livida was originally described based on an adult female specimen from Myanmar, but the original description lacked information on numerous morphological characters, coloration in life, ecology, and any information on males. We report specimens from four localities in Thailand that are verified as this species based on matches to a fragment of the mitochondrial 16S rRNA gene from the neotype of O. livida (uncorrected pairwise distances of 0.00–0.83%). We provide the first description of adult males and coloration in life, revise the morphological diagnosis of the species based on observed variation, extend the known geographic range, and report ecological information for O. livida using the new Thai specimens.